Barriers and Facilitators of Family Meetings in Primary Palliative Care: Insights From Slovenia - BAJT Mirjam; JAGODIC KLIPŠTETER Lucija; ZELKO Erika (Slovenian Journal of Public Health)
Within palliative care, family meetings are recognised as the most effective practice for placing the patient and their family at the centre of care, thereby ensuring quality palliative care. The aim of this study was to determine how these meetings are conducted in primary healthcare and to identify the factors influencing them.